Time Folding • Folding Time - Cay Miller, Lisa (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Lisa Cay Miller is a pianist/composer/improviser and Artistic Director of the NOW Society. In this piece, she offers a poetic description of the technological challenges associated with a large-scale sequential improvisation project in which thirty-six musicians and two sound engineers collaborated with one another to produce a total of thirty-eight videos of improvised musical performances.